Towards a minimal conception of Transitional Justice. Issue 3 (9th November 2022) - Gentile, Valentina; Foster, Megan
Abstract: Transitional Justice (TJ) focuses on the processes of dealing with the legacy of large-scale past abuses (in the aftermath of traumatic experiences such as war or authoritarianism) with the aim of fostering domestic justice and creating the basis for a sustainable peace. TJ however also entails the problem of how a torn society may be able to become a self-determining member of a just international order. This paper presents a minimal conception of TJ, which departs from Rawls' conception of normative stability of the international order, which suggests disentangling the two goals of fostering democracy within torn societies and TJ itself. The scope of TJ is therefore limited to enabling these societies to create minimal internal conditions for joining a just international order on equal footing. This paper makes an original contribution to two different debates, namely normative research on TJ, and post-Rawlsian literature in general. First, it provides a new direction for normative theorizing about TJ which takes both its domestic and international dimensions seriously into consideration. Second, it extends Rawls' political liberal outlook to an area where it is not usually understood to apply.